Conceptual Model to Assess the Outreach Programmes Providing Education to Children - Rajput, Gunjan (Voices of Teachers and Teacher Educators, 2019)
Present paper is an attempt to develop a conceptual model to assess the effectiveness of the outreach programs, which are providing education to the children who are not able to attend formal schooling due to many reasons. The model was developed after analyzing three ground theories related to right to education; UNICEF’s Human rights based approach, Amartya Sen and Martha Nussbaum’s Capabilites approach and Piggozi’s two level model. The conceptual model explains as how the main concepts and ground theories are connected, defines the criteria to evaluate the outreach programs and measures the ability of the outreach programs in providing access to education on one hand and the extent to which these programs are able to help children in gaining skills, values and knowledge that will help them in escaping poverty and leading valuable lives on the other hand.